Narratives of Geography, Culture, and School Exclusion on the Indonesian Coast: Evidence from Kedabu Rapat, Meranti Islands - Achmad Hidir; Rahman Malik; Li Wei; Robi Armilus; Yusuf Krisman Gea; Mardatillah Mardatillah (International Journal of Educational Narratives, 2026)
Background. In coastal 3T regions, referring to remote, outermost, and disadvantaged areas, access to basic education is still not simple. The policy looks clear on paper, but village life is more complicated. Free tuition helps, yet distance, transport cost, family work, and local views about schooling still shape the decision of parents. Earlier studies have discussed these issues, but fewer have shown how distance and culture meet in everyday coastal families. Purpose. This research describes the social, cultural, economic, and geographical barriers that limit children's access to school and madrasah education in Kedabu Rapat Village, Kepulauan Meranti. Method. The research used a quantitative descriptive design. Data were collected from 48 farming and fishing households selected through simple random sampling from 96 households with school-aged children. The data were analyzed through frequencies and percentages. Results. Households with three to four school-aged children had the highest dropout proportion. In this group, 13 of 23 households, or 56.52%, reported children who no longer attended school. In the whole sample, 18 of 48 households, or 37.50%, reported dropout cases. Low parental motivation appeared in 33.34% of responses. The most common barrier was the combination of school distance and sociocultural belief, reported by 56.26% of respondents. Conclusion. Geographical isolation creates more than a travel problem. It also makes farming and fishing look more practical than schooling, especially when family income is uncertain and the road to school is not easy.